OPTIMASI PRODUKSI DENGAN MELAKUKAN RE-DESIGN TUBING ID PADA SUMUR “REDD-24” LAPANGAN “ANANDA” SETELAH DILAKUKAN PENGASAMAN - Ananda, Muhammad Rafly; Manik, Nijusiho; Sera, Rohima; Jumardi, Andi; Fatma, Fatma; Caesar, Abiyyu (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The length of time to produce reservoir fluid will definitely experience a decrease in the production rate. The decrease in production rate can be caused by inappropriate tubing sizes and Damage to formations that impede fluid flow.To overcome the decline in production rates, it is necessary to choose the appropriate tubing size and carry out acidizing activities. Appropriate tubing size can avoid pressure drop and extend the life of the well. Acidizing is the injection of acid to eliminate the effect of decreasing permeability. The tubing size of 2 7/8 inches is not suitable for the “REDD-24” well because the target Qopt value of 130.997 bfpd was not achieved and there was an indication of calcium carbonate scale in the formation. This study discusses production optimization by re-designing tubing id after acidizing. Calculating the inflow performance relationship (IPR) using the Wiggin's method and obtaining Qtmax results of 163.74583 bpd, calculating theProductivity Index (PI) of 0.0870911 psi which according to Kermit E. Brown, the PI value is classified as low, calculates the skin value and obtains the results (+) 37.35 which indicates that the formation of the "REDD-24" well has suffered formation Damage. Selection of tubing with Hagedorn & Browns's correlation, analyzing Qopt tubing sizes of 3 1/2 inches, 2 inches, 1 2/3 inches, and 1 1/3 inches. Choose tubing with a size of 1 1/3 inches. matrix acidizing planning by knowing the value of formation fracture pressure (Pf) of 4857 psi, maximum  injection rate (Imax) of 2.829 bbl/min, maximum injection pressure (Pmax) of 1318.24, injected acid volume of 42.13561 bbl, and knowing success rate.